An alternative theoretical model of the Earth's EM field based on two-component field hypotheses - Bjelić, Slobodan N.; Marković, Nenad A. (Vojnotehnički glasnik / Military Technical Courier, 2023)
Introduction/purpose: The paper describes an alternative theoretical model of the Earth's EM field based on two-component field hypotheses. The paper consists of several parts, one part of which is a model showing the rotation of the magnetically conducting sphere of magnetization M in a foreign magnetic field. The last part defines theoretical models for the calculation of the components of the electromagnetic field of electrically conductive, dielectric and magnetically conductive spheres which are exposed to the influence of a foreign electromagnetic field.Methods: In the work, the responses of electrically conductive, dielectric and magnetically conductive spheres to the influence of external EM fields were investigated using the analytical method.Results: The obtained solutions in the form of analytical formulas will be applied to research the impact of the Sun's EM field on the planets and especially on the Earth.Conclusion: The resulting formulas of the electric and magnetic field strength and induction and their solutions can be applied to electrically conductive, dielectric and magnetically conductive spheres. In comparison to already known formulas, they are simple and have higher accuracy.
Keywords: theory; model; electromagnetism; components; spheres; rotation; magnetic field